Moving forward together : NSW Aboriginal Mental Health Conference, 1-3 September 1999 - NSW Aboriginal Mental Health Conference 1999 : Penrith, N.S.W.); Link-Up (NSW) Aboriginal Corporation; New South Wales. Department of Health. Centre for Mental Health; Aboriginal Health and Medical Research Council of NSW. ([North Sydney, N.S.W.] : Centre for Mental Health, NSW Dept. of Health, 1999)
Annotation pending.
Cover title.
"April 2002"--Verso of cover.
"Aboriginal Health & Medical Research Council of New South Wales, LINK-UP (NSW), NSW Health"
Includes bibliographical references.
Keywords: Aboriginal Australians -- Mental health -- Congresses; Aboriginal Australians -- Mental health services -- Congresses; Aboriginal Australians -- Mental health -- New South Wales -- Congresses; Aboriginal Australians -- Mental health services -- New South Wales -- Congresses; Health services - Health workers - Training; Mental health - Suicide; Mental health - Services; Child welfare - Care services; Child welfare - Child / parent separation - Stolen generations; Mental health - Dementia; Politics and Government - National symbols and events - Apologies - Stolen generations; Health - Education and promotion; Education - Skills and curriculum - Cultural awareness; Psychology - Therapy and counselling - Grief and trauma; Mental health - Depression